Lexical decision and eye tracking in the reading of words with prefixes, roots, and suffixes with transposed letters - Saguie, Aline (2018)
The present work intends to contribute to advance the debate between the holistic and decompositional models of morphological processing, investigating the impact of the transposition of letters in the processing of words. The focus of the research was to evaluate if there are differences in processing, depending on the position of the transposed letters, among the morphemes that make up the words, i.e. in the prefix, in the root or in the suffix. For this purpose, a classic lexical decision experiment and a lexical decision experiment monitored by an eye-tracker were performed. The results of the first experiment would indicate only a suffix recency effect in the lexical decision, whereas the online results of the eye-tracking experiment allowed to differentiate the average fixation times in the regions of prefixes, roots and suffixes (Root> Suffix> Prefix), adding evidence in favor of morphological decomposition prior to lexical access.